P17 National antimicrobial point prevalence survey in adult inpatient mental health facilities in Ireland. (19th January 2023) - Fagan, S; Donnelly, M; Clancy, A; Regan, M; Maher, A M; Ryan, C; Armitage, S; Shah, M; Sheehan, P; Mannion, C; Gallagher, O; Foran, R; et al.
Abstract: Background: Antimicrobial use in mental health inpatient settings has not been extensively examined in Ireland. The Healthcare-Associated Infection and Antimicrobial Use in Long-Term Care Facilities (HALT) study 2016 found that Irish long-term care facilities caring for residents with psychiatric conditions had an antimicrobial prevalence rate of 7.7%, higher than the European average of 4.9%. National community antimicrobial prescribing guidelines are available at www.antibioticprescribing.ie . In addition, a preferred antibiotic initiative for community settings advocates prescribers to choose 'Green' (preferred) antibiotics over 'Red' (reserved) agents. Reserved agents are considered to have more adverse effects, drug interactions and potential for development of antimicrobial resistance. The patient safety implications of antimicrobial stewardship along with an ageing population, and potential drug–drug interactions between many antimicrobials and psychotropic medications prompted a review of antimicrobial use practices in mental health services. Methods: A sample of adult inpatient mental health facilities (MHF) operated by the state's Health Service Executive (HSE) were surveyed by community antimicrobial pharmacists (AMPs) between November 2021 and January 2022. AMPs reviewed patients' medication charts for systemic antimicrobial prescriptions in the previous 30 days in addition to medical notes and laboratory results (where available). Adherence to HSE National community antimicrobial guidelines and the systems and structures in place to support antimicrobial stewardship were assessed. Results: In total, 1003 patients in 51 MHFs were surveyed. At the time of survey, 6.3% ( n =66) patients were on a systemic antimicrobial and 15% ( n =153) had received a systemic antimicrobial within the previous 30 days. Prophylaxis accounted for 50% of antibiotic use (3.3% of all patients), with the most common indication being the prevention of urinary tract infection (UTI) (58%). Prophylaxis duration exceeded six months in 61% of prescriptions. The median duration of treatment courses was seven days. The proportion of 'Green' (preferred) antimicrobials versus 'Red' (reserved) antimicrobials was 58% versus 38%. Co-amoxiclav, a 'Red' agent was the most commonly prescribed antibiotic for treatment of infection (31%). Adherence with choice of antimicrobial agent as per national antimicrobial guidelines was 76%; adherence of dosing regimen was 75% and adherence with recommended duration was 46%. The main themes for non-adherence with choice of agent were use of unnecessarily broad spectrum agents, nitrofurantoin prescribed in renal impairment and inappropriate formulation of nitrofurantoin chosen. Dipstick urinalysis was performed routinely (on admission and/or at designated intervals) for persons asymptomatic of UTI in 53% ( n =27) of MHFs. Conclusions: This PPS established antimicrobial use practices in HSE MHFs and identified opportunities for improvement relating to the safe and optimal use of antimicrobials. Key national recommendations from this survey were: Patients on urinary antibiotic prophylaxis ≥6 months should be reviewed with a view to de-prescribing. Routine use of dipstick urinalysis for asymptomatic patients to support diagnosis of UTI should cease. All nursing and medical staff should be aware of national antimicrobial prescribing guidelines for community published on www.antibioticprescribing.ie . Where an antimicrobial is considered necessary, a 'Green' agent (preferred) should be selected instead of a 'Red' agent (reserved) where possible. Prescribe the shortest effective duration for antimicrobials.